Aprosdokitos mikrotero gen. et sp. nov., the tiniest Sphenisciformes that lived in Antarctica during the Paleogene - Acosta Hospitaleche, Carolina Ileana Alicia; Reguero, Marcelo Alfredo; Santillana, Sergio (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
A small humerus from Eocene levels of Seymour Island, Antarctica is assigned here to Aprosdokitos mikrotero sp. and gen. nov. (Aves, Sphenisciformes), based predominantly on its small size. An ontogenetic series based on Pygoscelis antartica was established for comparative purposes, and evaluation of pathological conditions was also carried out in order to rule out other possible sources of size variation. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Facultad de Ciencias Naturales y Museo, Universidad Nacional de la Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Reguero, Marcelo Alfredo. Facultad de Ciencias Naturales y Museo, Universidad Nacional de la Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina